The impact of involved node, involved field and mantle field radiotherapy on estimated radiation doses and risk of late effects for pediatric patients with Hodgkin lymphoma. Issue 4 (25th November 2013) - Maraldo, M.V.; Jørgensen, M.; Brodin, N.P.; Aznar, M.C.; Vogelius, I.R.; Petersen, P.M.; Berthelsen, A.K.; Christensen, C.B.; Hjalgrim, L.L.; Specht, L.
<x xml:space="preserve">Abstract</x> Background The use of radiotherapy (RT) is debated for pediatric patients with Hodgkin lymphoma (HL) due to the late effects of treatment. Radiation doses to the thyroid, heart, lungs, and breasts are compared with the extensive mantle field (MF), Involved Field RT (IFRT), Modified IFRT (mIFRT), and Involved Node RT (INRT) and the risk of radiation‐induced cardiovascular disease, secondary cancers, and the corresponding Life Years Lost (LYL) is estimated with each technique. Procedure INRT, mIFRT, IFRT, and MF plans (20 and 30 Gy) were simulated for 10 supradiaphragmatic, clinical stage I–II classical HL patients ≤18 years old, total of 4 × 2 plans for each patient. The lifetime excess risks of cardiac morbidity, cardiac mortality, lung, breast, and thyroid cancer with each technique were estimated. The estimated excess risks attributable to RT were based on HL series with long‐term follow‐up, treating death from other causes as competing risks. The corresponding LYL were derived from the estimated excess risks. Statistical analyses were performed with repeated measures ANOVA. Results Both a reduction in field size and in prescribed radiation dose significantly lowered the estimated dose to the heart, lungs, breasts, and thyroid compared to past, extended fields, even for patients with mediastinal disease. This translated into a significantly reduced estimated risk of cardiovascular disease, secondary cancers, and LYL. Conclusions Involved Node Radiotherapy should be considered for pediatric patients with Hodgkin lymphoma since it is estimated to substantially lower the risk of severe long‐term complications. Pediatr Blood Cancer 2014;61:717–722. © 2013 Wiley Periodicals, Inc.